y + 2x < 4x - 3 <em>subtract 2x from both sides</em>
y < 2x - 3
y = 2x - 3
for x = 0 → y = 2(0) - 3 = 0 - 3 = -3 → (0, -3)
for x = 2 → y = 2(2) - 3 = 4 - 3 = 1 → (2, 1)
dotted line and shading below a line
Answer:
the answer is c
Step-by-step explanation:
because it doesn't repeat the same number for example if it was two -1s it wouldn't be a function but positive and negative are different so yeah
Answer:
x = 10
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define</u>
6(x - 1) = 9(x - 4)
<u>Step 2: Solve for </u><em><u>x</u></em>
- Distribute: 6x - 6 = 9x - 36
- Subtract 6x on both sides: -6 = 3x - 36
- Isolate <em>x</em> term: 30 = 3x
- Isolate <em>x</em>: 10 = x
- Rewrite: x = 10
<u>Step 3: Check</u>
<em>Plug in x into the original equation to verify it's a solution.</em>
- Substitute in <em>x</em>: 6(10 - 1) = 9(10 - 4)
- Subtract: 6(9) = 9(6)
Here we see that the 2 expressions are exactly the same.
∴ x = 10 is the solution to the equation.